1976
DOI: 10.1104/pp.58.3.283
|View full text |Cite
|
Sign up to set email alerts
|

An NADP-dependent Glutamate Dehydrogenase in Chloroplasts from the Marine Green Alga Caulerpa simpliciuscula

Abstract: NADP-dependent glutamate dehydrogenase was partiafly purified from extacts of the marine siphonous green alga Caulrpa simpliciuscula. The enzyme had an apparent Km NH4+ of 0.4 to 0.7 mm and was highly specific for NADPH, a-ketoglutarate, and ammonium ions.The bulk of the NADP-gutamate dehydrogenase was isolated with the chloroplast fraction in cell-free preparations of this alga and was released from these "chloroplast fractions" as a soluble enzyme on gende lysis of chloroplast membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
2

Year Published

1978
1978
1990
1990

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 21 publications
0
19
2
Order By: Relevance
“…Although the P. laminosum enzyme was purified more than 4,400-fold, the preparation was not homogeneous when analyzed by polyacrylamide gel electrophoresis, indicating that this protein was present in a very low concentration even in ammonium-grown cells. However, the purified enzymes from other sources showed lower specific activities (between 3.5 and 8.5 U/mg of protein) (11,17) and were less highly purified (78-and 6-fold, respectively). Our enzyme recovery compares to that of the enzyme from the fungus Cenococcum graniforme (25) but is much lower than that of Chlorella spp.…”
Section: Discussionmentioning
confidence: 92%
“…Although the P. laminosum enzyme was purified more than 4,400-fold, the preparation was not homogeneous when analyzed by polyacrylamide gel electrophoresis, indicating that this protein was present in a very low concentration even in ammonium-grown cells. However, the purified enzymes from other sources showed lower specific activities (between 3.5 and 8.5 U/mg of protein) (11,17) and were less highly purified (78-and 6-fold, respectively). Our enzyme recovery compares to that of the enzyme from the fungus Cenococcum graniforme (25) but is much lower than that of Chlorella spp.…”
Section: Discussionmentioning
confidence: 92%
“…This may apply in the case of the alga Caulerpa sirnpliciuscula (Gayler and Morgan, 1976;McKenzie et al. 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were har-(1976) and Turpin and Harrison (1978) further support vested during the exponential phase of growth except this view. Thus while GDH activity might be of prime in the case of Isochrysis galbana in which senescent importance in nitrogen assimilation in organisms such cells were assayed because they exhibited greater as Caulerpa simpliciuscula (Gayler and Morgan, 1976; levels of GS activity. McKenzie et al, 1979) and in Stichococcus bacillaris (Everest and Syrett, in press), it appears to play only a secondary role in marine phytoplankton.…”
Section: Methodsmentioning
confidence: 99%
“…It had been previously shown that C. simplicwscula chloroplasts contained an NADP-dependent glutamate dehydrogenase with a low Km for ammonia (5). This unusual glutamate dehydrogenase has now been shown to be augmented by similar levels of the conventional glutamine synthetase and GOGAT.…”
Section: Discussionmentioning
confidence: 89%